The Role of Artificial Intelligence Literacy in Building an Inclusive Digital Society - Hisbullah, Hisbullah; Faisal, Muhammad (Jujurnal Publisher, 2024)
The development of Artificial Intelligence (AI) has accelerated digital transformation in various sectors, but also presents challenges in the form of competency gaps, ethical risks and unequal access to technology. This research aims to analyze the role of AI literacy in building an inclusive digital society. The research uses qualitative methods with a literature study approach through analysis of various reputable scientific articles, academic books and relevant international policy documents. Data were analyzed using qualitative content analysis techniques to identify themes, patterns and relationships between concepts. The research results show that AI literacy is a multidimensional competency that includes cognitive, technical, critical, ethical and social aspects. Mastery of these competencies contributes to expanding access to digital services, increasing participation in the digital economy, reducing the digital divide, and strengthening society's capacity to face the risks posed by the use of AI. However, its implementation still faces challenges in the form of infrastructure inequality, low distribution of literacy programs, and the complexity of AI governance and ethics. Therefore, strengthening AI literacy through education, lifelong learning, multi-stakeholder collaboration and Responsible Artificial Intelligence policies is an important strategy for realizing an inclusive, adaptive and sustainable digital society.